Ferdinand Duchatsch - slovenski Nemec oziroma nemški Slovenec - Zajšek, Boštjan (Studia Historica Slovenica, 2017)
This piece presents the political life and work of mayor Ferdinand Dachatsch, doctor of law and politician. The main sources for the piece are taken from contemporary German and Slovenian newspapers and records from the meetings of the Maribor Municipal Council. The author especially emphasises Dachatsch's duality in the sense of national allegiance. Even his contemporaries noted that he was Slovenian by origin, but considered himself German, although he would occasionally, especially at prelection rallies, emphasise his Slovenian origin. Duchatsch was a municipal councillor in Maribor for many years; he was also elected to the Provincial Assembly and State Parliament. Alongside political activity, his social activity is also presented in the piece.
Keywords: 19.st.; Duchatsch, Ferdinand; Maribor; zgodovina; župani